Kinetic-model-free analysis of transient absorption spectra enabled by 2D correlation analysis - Hniopek, Julian; Mueller, Carolin; Bocklitz, Thomas; Schmitt, Michael; Dietzek, Benjamin; Popp, Juergen (Journal of Physical Chemistry Letters, 2021)
Here, we present, to the best of our knowledge for the first time, a systematic study of utilizing 2D correlation analysis in the field of femtosecond transient absorption (fs-TA) spectroscopy. We present that the application of 2D correlation spectroscopy (2DCOS) to fs-TA spectroscopy enables a model-free means to analyze excited state kinetics, which is demonstrated on the model system [(tbbpy)2Ru(dppz)]2+ in different solvents. We show that TA-2DCOS is able to determine the number of processes contributing to the time-resolved spectral changes in fs-TA data sets, as well as extract the spectral response of these components. Overall, the results show that TA-2DCOS leads to the same results as obtained with methods relying on global lifetime analysis or multivariate curve resolution but without the need to specify a predetermined kinetic model. The work presented therefore highlights the potential of TA-2DCOS as a model-free approach for analyzing fs-TA spectral data sets.
CRIS-Team Scopus Importer:2023-04-20